Implementasi Strategi Pembelajaran Aktif dalam Meningkatkan Partisipasi Siswa Sekolah Dasar di Kota Semarang - Innal Muarrifah; Lawnisa Adita; Mega Berliana; Naeli Ulfiyani; Ferina Agustini (PGRI Kota Semarang, 2026)
This study aims to analyze and describe the implementation of active learning strategies to increase student participation at Supriyadi Elementary School. The study used a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that various active learning models, such as Problem-Based Learning (PBL), Project-Based Learning (PjBL), Discovery Learning, and Cooperative Learning (STAD), have been implemented in an integrated manner. The implementation of these multiple models has been proven to significantly increase student participation, as indicated by increased questioning, involvement in discussions, and the ability to collaborate. These findings support recent research (2023–2024) which states that active learning based on student-centered learning is effective in increasing student engagement. Thus, the varied implementation of active learning strategies positively contributes to creating interactive, innovative, and meaningful learning.